Genetic and infective diversity of the liver fluke Fasciola hepatica (Trematoda: Digenea) from Cuba. Issue 6 (14th January 2016) - Vázquez, A.A.; Lounnas, M.; Sánchez, J.; Alba, A.; Milesi, A.; Hurtrez-Boussès, S.
Abstract: In this study we present the first approach to exploration of the genetic diversity of Cuban Fasciola hepatica populations using microsatellite markers, coupled with observed prevalence in slaughterhouses. Nine populations of flukes recovered from cows and buffalos were studied in the central-western region of Cuba. The observed infection rates of definitive hosts (bovines) were 70–100% in most cases. An important amount of polymorphism was found in the four loci explored. However, no apparent genetic differences were found between populations from different provinces or bovine species. The absence of deviations from Hardy–Weinberg equilibrium suggests a high rate of cross-fertilization between F. hepatica individuals. This result was confirmed when all multilocus genotypes were tested for clonal reproduction and only four individuals differed statistically ( P sex < 0.05). High values of expected heterozygosity coupled with highly probable mixing among strains make the metapopulation genetically diversified but similar in terms of certain alleles (low F ST values). These results suggest a close relationship between parasite diversity and cattle management in Cuba. Our findings should be taken into consideration by veterinary authorities to help mitigate fasciolosis transmission.